Sosialisasi dan Pendampingan Lesson Study di SMAN 2 Kotabumi: Menuju Peningkatan Profesionalisme Guru - Purna Bayu Nugroho; Rulik Setiani; Dewi Ratnaningsih; Elis Susanti; Ratih Handayani; Darwanto; Asep Hardiyanto (Pengabdian Kepada Masyarakat Cendekia, 2024)
Lesson Study is an activity conducted to improve the quality of teaching. As a collaborative approach, Lesson Study consists of stages such as planning, implementation, evaluation, and reflection, with the aim of continuously enhancing the quality of teaching. Therefore, the community service team from Universitas Muhammadiyah Kotabumi (UMKO) held a socialization event on October 14, 2024, to introduce the concept and stages of Lesson Study. This activity involved UMKO lecturers who are experts in various fields of study, acting as facilitators and mentors, providing both theoretical knowledge and hands-on practice to teachers. The event is expected to improve teachers' understanding and skills in implementing Lesson Study and encourage them to continuously develop innovative and effective teaching methods. This program also facilitates collaboration among teachers from different subject areas and supports the creation of a productive learning community at SMAN 2 Kotabumi. The outcome of the Lesson Study socialization activity at SMAN 2 Kotabumi shows a significant improvement in teachers' understanding of the fundamental concepts and practical application of Lesson Study.